How Near Will You Hear? A Response to Benadon, "Near-unisons in Afro-Cuban Ensemble Drumming" - Martens, Peter (Empirical Musicology Review, 2017)
Fernando Benadon (2016) shines a strong objective light onto slight but noticeable timing perturbations in Afro-Cuban drumming practice, coining the term near-unisons to describe non-simultaneous attacks that are perceived as such, but that are also perceived to correspond to the same point on an abstract isochronous grid. I speculate that these data uncover an aspect of the music that will most likely be perceived qualitatively rather than quantitatively—an element of style rather than one of structure—but that the quantitative approach taken here is a crucial first step toward the stylistic analysis of genre-specific microtiming that is generally painted over with the broad brushes of participatory discrepancy or groove.